The Relationship Between Learning Motivation and Learning Outcomes of 3 IN 1 Training Participants of Manual Embroidery Clothing - Reno Nilam; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the low learning outcomes of the training participants who participated in the 3 in 1 manual embroidery fashion decoration training at the Padang Industrial Training Center. This is presumably because the trainees have low motivation. The purpose of this study was to see (1) a description of the learning motivation of the training participants in participating in the 3 in 1 manual embroidery fashion decoration training. (2) description of the learning outcomes of participants in 3 in 1 manual embroidery fashion decoration training (3) the relationship between learning motivation and learning outcomes of participants in 3 in 1 manual embroidery fashion decoration training at the Padang Industrial Training Center. This research is a correlational study with a quantitative approach. The population of this study was 70 training participants and the sample in this study was taken as much as 50% or consisted of 35 training participants using the stratified cluster random sampling method, data collection using questionaires and tools in the form of a list of statements. Analysis tecnique uses the percentage and product moment. The results of this study indicate that: (1) the description of the learning motivation of 3 in 1 training participants with manual embroidery decorations at the Padang industrial training center is low. (2) the learning outcomes of the 3 in 1 training participants in manual embroidery decoration at the Padang Industrial Training Center are low. (3) there is a significant relationship between learning motivation and learning outcomes of 3 in 1 training participants in manual embroidery fashion decoration at the Padang Industrial Training Center. It is expected that the manager can provide facilities and interesting learning methods so as to increase the motivation of participants in training activities so that it can affect their learning outcomes.